Mayflower a voyage to war - Philbrick, Nathaniel (HarperPress, 2006)
From the perilous ocean crossing to the shared bounty of the first Thanksgiving, the Pilgrim settlement of New England has become enshrined as our most sacred national myth. Yet, as author Philbrick reveals, the true story of the Pilgrims is much more than the well-known tale of piety and sacrifice; it is a 55-year epic. The Mayflower's religious refugees arrived in Plymouth Harbor during a period of crisis for Native Americans, as disease spread by European fishermen devastated their populations. Initially the two groups maintained a fragile working relationship. But within decades, New England erupted into King Philip's War, a savage conflict that nearly wiped out colonists and natives alike, and forever altered the face of the fledgling colonies and the country that would grow from them. Philbrick has fashioned a fresh portrait of the dawn of American history--dominated right from the start by issues of race, violence, and religion